A República da Puçanga: farmácia, farmacêuticos e as artes de curar em Belém do Pará (1889-1905) - SILVA, Karla Yasmim Ferreira da (2024)
The aim of this work is to reflect on the universe of healing and the work of the various medicine formulators, demonstrating that doctors and pharmacists, during the republican regime in Pará, competed for space with subjects without academic training. In order to do this, we sought to analyze the hypotheses raised, taking into account the time frame from the establishment of the Republic (1889) to 1905, when the state government inaugurated and consolidated the first Pharmacy School in Belém. The methodology, of a qualitative nature, considered bibliographical research and historical sources gathered from digital and physical collections. During the republican regime in Belém, in the name of science and the interests of doctors and pharmacists, there was an intensified fight against the healing arts of popular tradition, moving them to the margins of legislation and placing them in the category of illegal medical practices. Without a license or academic training to work in this field, healers, midwives, shamans and many others were accused of practicing medicine illegally. However, although this fight took place on several fronts, it was not defined in a single blow, as it went through several phases of conflict and negotiation. The insistence of the popular healing arts on remaining very much alive in the midst of so many attacks was linked to their strong demand from the population and, as was the case with pharmacy practitioners, to the ambiguity of the republican legislation itself, which allowed them to operate freely. Therefore, in the early decades of the Republic, these institutions were still far from being fully medicalised spaces. The Republic that exalted science was, in fact, a voracious consumer of "puçanga". Thus, the history of pharmacy, pharmacists and medicines in the Amazon cannot be understood apart from the conflicts taking place in society. The history of science itself, far from being an evolutionary and victorious epic, has always been permeated with conflicts and resistance involving different conceptions of the world, just like any human history.